Reflectance spectral characterization and mineralogy of acid sulphate soil in subsurface using hyperspectral data - Shi, Xianzhong; Aspandiar, Mehrooz; Oldmeadow, D. (Guoji Nisha Yanjiu Zhongxin, 2014)
Acid sulphate soil (ASS) is a kind of soil which is harmful to the environment. ASS is hard to efficiently assess efficiently in the subsurface, although it is detectable on the surface by remote sensing. This paper aims to explore a new way to rapidly assess ASS in the subsurface by introducing a proximal hyperspectral instrument, namely the Hylogger™ system which can rapidly scan soil cores and provide high resolution hyperspectral data. Some minerals in ASS, which usually act as indicators of the severity of ASS, such as iron oxides, hydroxides, and sulphates, as well as some clay minerals, such as kaolinite, have diagnostic spectral absorption features in the reflectance spectral range (4002500 nm). Soil cores were collected from a study area and hyperspectral data were acquired by Hylogger™ scanning. The main minerals related to ASS were characterized spectrally, and were subsequently identified and mapped in the soil cores based on their reflectance spectral characteristics. Traditional X-ray diffraction (XRD) and scanning electron microscope (SEM) were also applied to verify the results of the mineral identification. The main results of this study include the spectral characterisation of ASS and its main compositional minerals, as well as the distribution of these relevant minerals in different depth of cores.